2002
DOI: 10.14356/kona.2002021
|View full text |Cite
|
Sign up to set email alerts
|

Particle Shape Modification in Comminution

Abstract: The evolution of particle shape during the course of comminution processes has been investigated. Shape is characterized using a variety of quantitative shape descriptors determined from particle profiles obtained by image analysis. Descriptors related to particle elongation, roundness and angularity are emphasized. Distributions of the descriptors have been determined for a range of particle sizes, for different extents of grinding for various equipment types. For a given descriptor, the distributions of meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 6 publications
4
23
0
Order By: Relevance
“…This implies that the shape of particles is controlled by the milling time, which is in agreement with the observations of Kaya et al [15] for quartz and coal. However Kaya et al [15] have reported that grinding in a planetary ball mill produces more rounded particles with increasing milling time without increasing elongation ratio till 6 h of milling time followed by a decrease.…”
Section: Particle Size and Shapesupporting
confidence: 92%
See 1 more Smart Citation
“…This implies that the shape of particles is controlled by the milling time, which is in agreement with the observations of Kaya et al [15] for quartz and coal. However Kaya et al [15] have reported that grinding in a planetary ball mill produces more rounded particles with increasing milling time without increasing elongation ratio till 6 h of milling time followed by a decrease.…”
Section: Particle Size and Shapesupporting
confidence: 92%
“…However Kaya et al [15] have reported that grinding in a planetary ball mill produces more rounded particles with increasing milling time without increasing elongation ratio till 6 h of milling time followed by a decrease. Also, the observations of the authors are not in agreement with Kuga et al [16] who however used a screen mill for comminution.…”
Section: Particle Size and Shapementioning
confidence: 97%
“…Particles that are more angular with high asperities and high aspect ratio are selectively comminuted. Similar findings have been made by Kaya et al (2002) where they found that single breakage events often result in irregularly shaped particles while multiple breakage events lead to the production of relatively round particles. Forssberg and Zhai (1985) showed that particles produced from autogenous mills are more rounded than those from conventional ball and rod mills due to the abrasion effect.…”
Section: Effect Of Breakage Mechanism On Particle Shapesupporting
confidence: 85%
“…With increasing pulverization residence time (of an hour or more), however, the shapes of the particles are altered towards more spherical or "blocky type" shapes 19) . Also, there is evidence that different methods of pulverization produce different particle shapes 4,5,20) , although one study found little influence of pulverizer type upon shape 21) . Extended comminution time has also been shown to influence particle shape 20) for most of the devices used, the exception was a high-energy mill.…”
Section: Resultsmentioning
confidence: 99%
“…Also, there is evidence that different methods of pulverization produce different particle shapes 4,5,20) , although one study found little influence of pulverizer type upon shape 21) . Extended comminution time has also been shown to influence particle shape 20) for most of the devices used, the exception was a high-energy mill. Lithotypes also have different friabilities, with the monomaceral microlithotypes of vitrinite and inertinite being the easiest to grind under Hardgrove grindability conditions, thus, increasing the concentration of trimaceral lithotypes in the coarser grinds 22) .…”
Section: Resultsmentioning
confidence: 99%